Biometrical Studies on the Liver of Sheep during Prenatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on liver of embryo/fetuses to investigate the biometrical changes during prenatal development. The prenatal liver were divided into three groups. A progressive increase with age in average weight of the fetus, weight of the liver, volume of the liver, length of whole liver, distance from esophageal notch to umbilical fissure. The average length and width of right lobe of liver was higher than that of the left lobes in all the prenatal groups. The length, width and thickness of caudate, papillary and quadrate lobes of liver showed a progressive increase with age.